INFORMATION MODEL OF THE RESEARCH OBJECT IN MEDICAL DECISION SUPPORT SYSTEMS - Мунтян, Максим; Мунтян, Ольга; Яровенко, Анатолий (SWorldJournal, 2021)
The paper considers the method of constructing an information model of the research object on the basis of a theoretical-multiple approach for the formation of a database of models for medical SPR diagnostic type